PENGARUH TUTUPAN LAHAN TERHADAP RETENSI AIR DAN KONSERVASI TANAH DI HUTAN TROPIS: SUATU KAJIAN LITERATUR - Najmah Fairuz Zahira; Hijratun Nugraha Tri Putri; Anissa Dinda Lestari; Eni Nuraeni (JURNAL BIOSENSE, 2026)
Land cover plays an essential role in maintaining hydrological balance and soil conservation in tropical forest ecosystems. The decline in vegetation cover can lead to reduced infiltration, increased surface runoff, and decreased soil water-holding capacity. This literature review aims to analyze the relationship between land cover, water retention, and soil conservation in tropical forests based on recent scientific findings. The analysis includes studies on soil biophysical properties, rainfall, vegetation types, and forest management strategies. The results indicate that dense and multi-layered vegetation improves soil porosity, infiltration, and water retention while reducing erosion. In contrast, the degradation of vegetation cover decreases soil physical quality and hydrological stability. Effective conservation efforts include the implementation of agroforestry systems, integrated watershed management, and sustainable forest protection policies.